Effect of light attenuation through veneers on bond strength of adhesives with photoinitiator combinations - Jamille FAVARÃO; Dayane Carvalho Ramos Salles de OLIVEIRA; Mauricio Matté ZANINI; Mateus Garcia ROCHA; Fabrício Aulo OGLIARI; Lourenço CORRER-SOBRINHO; Mário Alexandre Coelho SINHORETI (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study aimed to evaluate the effect of light attenuation through ceramic veneers and resin cement on degree of conversion (DC), cohesive strength (CS), and microshear bond strength (μSBS) of experimental adhesive systems. Experimental etch-and-rinse and self-etch adhesives were combined with different ratios of camphorquinone (CQ) and diphenyl(2,4,6-trimethylbenzoyl) phosphine oxide (TPO) photoinitiators: CQ-only; 3CQ:1TPO; 1CQ:1TPO; 1CQ:3TPO and TPO-only. Square-shaped ceramic veneer (IPS Empress Esthetic, Ivoclar Vivadent) (n = 10; 10mm long x 10mm wide x 0.5mm thick) and resin cement specimens (Variolink Esthetic LC, Ivoclar Vivadent) (n = 10; 10 mm long x 10 mm wide and 0.3 mm thick) were prepared. Light transmittance of a multiple-peak LED (Bluephase G2, Ivoclar Vivadent) was measured through restorative materials using a spectrometer (n = 5). Adhesive specimens were analyzed for DC, CS, and μSBS by light-curing the adhesive with or without (control) ceramic veneer, and with resin cement fixed to output region of the light-curing tip (n = 10). Data were submitted to ANOVA and Tukey's test (α = 0.05). Total light transmittance through the restorative materials was attenuated, and this attenuation was more evident for the violet spectrum. The DC for the TPO groups in ratios up to 1CQ:1TPO was similar to the control. 1CQ:3TPO showed lower values for CS. μSBS was reduced for all groups with light attenuation, but lower values were observed for 1CQ:3TPO and TPO-only. In conclusion, light transmission was reduced with interposed restorative materials. Adhesives combined with CQ and TPO up to 1CQ:1TPO showed greater cure efficiency and mechanical properties compared with a higher amount of TPO.